2006
DOI: 10.1029/2005jb004257
|View full text |Cite
|
Sign up to set email alerts
|

Flow of synthetic, wet, partially molten “granite” under undrained conditions: An experimental study

Abstract: [1] Major problems in experimental studies of the flow of partially molten granitic rocks are (1) maintaining control of the grain size of the matrix of solid grains, (2) controlling the melt fraction, and (3) controlling the melt viscosity (closely linked to water content). To overcome these problems, we used a synthetic ''granitoid'' comprising a solid matrix of quartz grains (50 mm grain size) mixed with an albite-quartz melt prepared from oxides, with added water (2.5 wt %) dissolved in the melt phase (vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 38 publications
(59 reference statements)
0
47
0
Order By: Relevance
“…This inversion of the relationship between the τ c and magma crystallinity can be reconciled with microscopic processes (Figures 2C,D). Once φ reaches about 0.4-0.5, shear-thinning behavior is observed because local dilation and compaction are required for magmas to flow at such high crystallinity (Rutter et al, 2006;Caricchi et al, 2007;Pistone et al, 2012). When the φ increases at constant β, the β/µ increases leading to a relative bubble enrichment in the melt phase.…”
Section: Discussion Empirical Quantification Of the Viscous To Brittlmentioning
confidence: 97%
“…This inversion of the relationship between the τ c and magma crystallinity can be reconciled with microscopic processes (Figures 2C,D). Once φ reaches about 0.4-0.5, shear-thinning behavior is observed because local dilation and compaction are required for magmas to flow at such high crystallinity (Rutter et al, 2006;Caricchi et al, 2007;Pistone et al, 2012). When the φ increases at constant β, the β/µ increases leading to a relative bubble enrichment in the melt phase.…”
Section: Discussion Empirical Quantification Of the Viscous To Brittlmentioning
confidence: 97%
“…On the other hand, experimental studies demonstrated that partial melting led to a general reduction in rock strength and concentrated deformation (Rutter et al, 2006;Mecklenburgh and Rutter, 2003;Kohlstedt and Zimmerman, 1996;Rutter and Neumann, 1995;Dell'Angelo et al, 1987). As shown by our experiment, the anisotropy enhanced by alignment of melt is likely comparable to or larger than that induced by LPO of rock-forming minerals.…”
Section: Aligned Melt Enhances Tibetan Crustal Anisotropymentioning
confidence: 52%
“…Melting occurring during a pervasive deformation episode will impart extreme weakening and ductile behaviour to rocks (e.g. Rosenberg and Handy 2005;Rutter et al, 2006), ultimately to the whole crustal section. This environment should promote widespread thinning in the subducting slab in which the Cabo Ortegal nappe was involved during plate convergence prior to the Variscan collision.…”
Section: Characteristics Of the Exhumation Of Cabo Ortegal Nappe Rocksmentioning
confidence: 99%
“…In the case of the Himalayan-Tibet system, the great crustal thickness beneath the Tibetan Plateau contributes significantly to the lithostatic pressure gradient required to force the lateral and frontal flow of a ductile lower crust (e.g. Beaumont et al, 2004;Rutter et al, 2011). Highly sheared and migmatized rocks of the greater Himalayan sequence between the Main Central Thrust and the South Tibetan Detachment are effectively extruded towards the foreland.…”
Section: Introductionmentioning
confidence: 99%